Skip to main content
Solve for m
Tick mark Image

Similar Problems from Web Search

Share

10m^{2}-996m+39600=0
All equations of the form ax^{2}+bx+c=0 can be solved using the quadratic formula: \frac{-b±\sqrt{b^{2}-4ac}}{2a}. The quadratic formula gives two solutions, one when ± is addition and one when it is subtraction.
m=\frac{-\left(-996\right)±\sqrt{\left(-996\right)^{2}-4\times 10\times 39600}}{2\times 10}
This equation is in standard form: ax^{2}+bx+c=0. Substitute 10 for a, -996 for b, and 39600 for c in the quadratic formula, \frac{-b±\sqrt{b^{2}-4ac}}{2a}.
m=\frac{-\left(-996\right)±\sqrt{992016-4\times 10\times 39600}}{2\times 10}
Square -996.
m=\frac{-\left(-996\right)±\sqrt{992016-40\times 39600}}{2\times 10}
Multiply -4 times 10.
m=\frac{-\left(-996\right)±\sqrt{992016-1584000}}{2\times 10}
Multiply -40 times 39600.
m=\frac{-\left(-996\right)±\sqrt{-591984}}{2\times 10}
Add 992016 to -1584000.
m=\frac{-\left(-996\right)±12\sqrt{4111}i}{2\times 10}
Take the square root of -591984.
m=\frac{996±12\sqrt{4111}i}{2\times 10}
The opposite of -996 is 996.
m=\frac{996±12\sqrt{4111}i}{20}
Multiply 2 times 10.
m=\frac{996+12\sqrt{4111}i}{20}
Now solve the equation m=\frac{996±12\sqrt{4111}i}{20} when ± is plus. Add 996 to 12i\sqrt{4111}.
m=\frac{249+3\sqrt{4111}i}{5}
Divide 996+12i\sqrt{4111} by 20.
m=\frac{-12\sqrt{4111}i+996}{20}
Now solve the equation m=\frac{996±12\sqrt{4111}i}{20} when ± is minus. Subtract 12i\sqrt{4111} from 996.
m=\frac{-3\sqrt{4111}i+249}{5}
Divide 996-12i\sqrt{4111} by 20.
m=\frac{249+3\sqrt{4111}i}{5} m=\frac{-3\sqrt{4111}i+249}{5}
The equation is now solved.
10m^{2}-996m+39600=0
Quadratic equations such as this one can be solved by completing the square. In order to complete the square, the equation must first be in the form x^{2}+bx=c.
10m^{2}-996m+39600-39600=-39600
Subtract 39600 from both sides of the equation.
10m^{2}-996m=-39600
Subtracting 39600 from itself leaves 0.
\frac{10m^{2}-996m}{10}=-\frac{39600}{10}
Divide both sides by 10.
m^{2}+\left(-\frac{996}{10}\right)m=-\frac{39600}{10}
Dividing by 10 undoes the multiplication by 10.
m^{2}-\frac{498}{5}m=-\frac{39600}{10}
Reduce the fraction \frac{-996}{10} to lowest terms by extracting and canceling out 2.
m^{2}-\frac{498}{5}m=-3960
Divide -39600 by 10.
m^{2}-\frac{498}{5}m+\left(-\frac{249}{5}\right)^{2}=-3960+\left(-\frac{249}{5}\right)^{2}
Divide -\frac{498}{5}, the coefficient of the x term, by 2 to get -\frac{249}{5}. Then add the square of -\frac{249}{5} to both sides of the equation. This step makes the left hand side of the equation a perfect square.
m^{2}-\frac{498}{5}m+\frac{62001}{25}=-3960+\frac{62001}{25}
Square -\frac{249}{5} by squaring both the numerator and the denominator of the fraction.
m^{2}-\frac{498}{5}m+\frac{62001}{25}=-\frac{36999}{25}
Add -3960 to \frac{62001}{25}.
\left(m-\frac{249}{5}\right)^{2}=-\frac{36999}{25}
Factor m^{2}-\frac{498}{5}m+\frac{62001}{25}. In general, when x^{2}+bx+c is a perfect square, it can always be factored as \left(x+\frac{b}{2}\right)^{2}.
\sqrt{\left(m-\frac{249}{5}\right)^{2}}=\sqrt{-\frac{36999}{25}}
Take the square root of both sides of the equation.
m-\frac{249}{5}=\frac{3\sqrt{4111}i}{5} m-\frac{249}{5}=-\frac{3\sqrt{4111}i}{5}
Simplify.
m=\frac{249+3\sqrt{4111}i}{5} m=\frac{-3\sqrt{4111}i+249}{5}
Add \frac{249}{5} to both sides of the equation.